2011
DOI: 10.1088/0957-4484/22/29/295703
|View full text |Cite
|
Sign up to set email alerts
|

Error in dynamic spring constant calibration of atomic force microscope probes due to nonuniform cantilevers

Abstract: Many common atomic force microscope (AFM) spring constant calibration methods regard the AFM probe as a uniform cantilever, neglecting the tip mass and any nonuniformity in the thickness of the probe along its length. This work quantifies the error in the spring constant estimated by the Sader and thermal calibration methods due to nonuniformity in the thickness of the cantilever and the influence of the mass loading effect of the probe tip. Formulae are presented that can be used to compute the uncertainty in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Since the fundamental mode shape is a simple monotonically increasing function of distance from the clamp, spatial variations in thickness and/or material have a weak effect on this mode shape and hence the general method. This explains recent theoretical findings demonstrating the robustness of the original method, with respect to thickness variations along the cantilever axis, in all but the extreme cases of very strong variations in thickness 32 -in these extreme cases, the mode shape was significantly altered. The same property holds true for the general method.…”
Section: Effect Of Non-uniform Cantilever Thickness and Materials Propsupporting
confidence: 72%
See 1 more Smart Citation
“…Since the fundamental mode shape is a simple monotonically increasing function of distance from the clamp, spatial variations in thickness and/or material have a weak effect on this mode shape and hence the general method. This explains recent theoretical findings demonstrating the robustness of the original method, with respect to thickness variations along the cantilever axis, in all but the extreme cases of very strong variations in thickness 32 -in these extreme cases, the mode shape was significantly altered. The same property holds true for the general method.…”
Section: Effect Of Non-uniform Cantilever Thickness and Materials Propsupporting
confidence: 72%
“…25,32 Nonetheless, if the imaging tip is comparable in size to the dominant hydrodynamic length scale of the flow, its presence will enhance the true energy dissipation and thus increase the hydrodynamic function. 24,25 While this can lead to an underestimate of the spring constant obtained using the original method, 25 the general method intrinsically accounts for any such extra energy dissipation.…”
Section: Effect Of Non-uniform Cantilever Thickness and Materials Propmentioning
confidence: 99%
“…Therefore the calibration of one cantilever would provide sufficient data to calculate the spring constant of the other cantilevers with accuracy of the order of 10% or better. However, the work presented by Frentrup and Allen showed that the thickness of the probe may vary along the probe, introducing a significant error while the determination bases on the assumption of perfect shapes of the probe [95]. Moreover, as presented by Webber et al the probes fashioned from that same wafer may differ even by factor of two [148], as the 101 V-shaped probes made of silicon nitride was measured using thermal spectrum method proposed by Hutter and Bechhoefer.…”
Section: Indirect Methodsmentioning
confidence: 99%
“…Also, the models assume shapes uniformity, as in case of the thickness, as critical parameter -it was shown that it may introduce a significant error [94,95]. The model taking into account this particular issue was presented by Fretrup and Allen, where effective thickness t es provides that same outcome that nonuniform probe where thickness profile is h(x) [95]:…”
Section: Theoretical Modelmentioning
confidence: 99%
See 1 more Smart Citation